2023
DOI: 10.1038/s41598-023-28743-5
|View full text |Cite
|
Sign up to set email alerts
|

Network-based validation of the psychometric questionnaire EDI-3 for the assessment of eating disorders

Abstract: Assessing the validity of a psychometric test is fundamental to ensure a reliable interpretation of its outcomes. Few attempts have been made recently to complement classical approaches (e.g., factor models) with a novel technique based on network analysis. The objective of the current study is to carry out a network-based validation of the Eating Disorder Inventory 3 (EDI-3), a questionnaire designed for the assessment of eating disorders. Exploiting a reliable, open source sample of 1206 patients diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Despite the underlying connections between psychometric network analysis and latent variable modeling (Kruis & Maris, 2016), the use of network psychometrics may have certain advantages, such as identifying the network structure of variables (i.e., nodes) and allowing the visualization of the strength of the (partial) correlations between variables (i.e., edges; Hevey, 2018). Thus, psychometric network analysis may provide new perspectives to evaluate the structure and dynamics of psychological tools in mental health settings, including tools for assessing eating behaviors (e.g., Laskowski et al, 2023;Punzi et al, 2023). For example, using psychometric network analysis, Laskowski et al (2023) revealed that the original factor model of the Eating Disorder Examination-Questionnaire (EDE-Q) might not be optimal for women with EDs; thus, they suggested using different scorings of the EDE-Q in women with EDs for screening purposes or for evaluating the effects of interventions.…”
Section: Psychometric Network Analysismentioning
confidence: 99%
“…Despite the underlying connections between psychometric network analysis and latent variable modeling (Kruis & Maris, 2016), the use of network psychometrics may have certain advantages, such as identifying the network structure of variables (i.e., nodes) and allowing the visualization of the strength of the (partial) correlations between variables (i.e., edges; Hevey, 2018). Thus, psychometric network analysis may provide new perspectives to evaluate the structure and dynamics of psychological tools in mental health settings, including tools for assessing eating behaviors (e.g., Laskowski et al, 2023;Punzi et al, 2023). For example, using psychometric network analysis, Laskowski et al (2023) revealed that the original factor model of the Eating Disorder Examination-Questionnaire (EDE-Q) might not be optimal for women with EDs; thus, they suggested using different scorings of the EDE-Q in women with EDs for screening purposes or for evaluating the effects of interventions.…”
Section: Psychometric Network Analysismentioning
confidence: 99%
“…Among these, the Eating Disorder Inventory (EDI) [ 5 , 6 ] and the Eating Disorder Examination (EDE) are prominent [ 7 ]. The EDI-3 is a standardized, self-report questionnaire assessing the main symptoms and psychological features of EDs [ 8 ]. The EDE-17 is a semi-structured, clinician-administered interview designed to evaluate specific aspects of ED psychopathology, as well as the severity of dysfunctional eating behaviors and attitudes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%